ANALISIS STRUKTUR DAN MAKNA CERITA ANAK SABALAH DAN ARUM BERISTRI TUAN BUNGSU ANAK RAJA (SASTRA LISAN DAYAK KANAYATN) - Priyadi, Antonius Totok; Khairullah, Khairullah; Elofhia, Loriya; Annisa, Ayu; Sabila, Lisa (Universitas Tanjungpura, 2025)
This research examines two Dayak Kanayatn folktales from Landak Regency, West Kalimantan, namely “Anak Sabalah” and “Arum Beristri Tuan Bungsu Anak Raja”. The purpose of this research is to find the storytelling environment, structure, and meaning of the story of